PENGEMBANGAN MEDIA TEKA -TEKI SILANG BERBASIS DIGITAL TERHADAP KEMAMPUAN MEMBACA PERMULAAN PADA ANAK KELAS B DI TK KEMALA BHAYANGKARI 1 PALEMBANG - Putri Salsabila; Mardiah Astuti; Izza Fitri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a digital crossword puzzle learning media to improve early reading skills in children aged 5–6 years in Class B at Kemala Bhayangkari 01 Kindergarten Palembang. The research was motivated by the low level of children's early reading ability and the limited use of technology-based learning media in early childhood education. This study used the Research and Development (R&D) method with the ADDIE development model which consists of Analysis, Design, Development, Implementation, and Evaluation stages. Data collection techniques included observation, interviews, expert validation questionnaires, teacher response questionnaires, and children's reading ability tests.The results showed that the developed digital crossword puzzle media met the criteria of validity, practicality, and effectiveness. The validity test results indicated that the media was categorized as very valid with an average score of 82.5% from material experts, 90% from language experts, and 92.85% from media experts. The practicality test conducted by teachers showed a maximum score of 55 out of 55 or 100%, indicating that the media was very practical to use in learning activities. Furthermore, the effectiveness test showed that the initial field trial achieved 92.5%, which increased to 93.67% in the main field trial. The hypothesis testing using the t-test obtained a t-count value of 8.519, which is higher than the t-table value of 0.443, indicating a significant effect of using digital crossword puzzle media on improving children's early reading skills.Therefore, the digital crossword puzzle media developed in this study is considered valid, practical, and effective for enhancing early reading skills in early childhood education.